2016
DOI: 10.3389/fnins.2016.00043
|View full text |Cite
|
Sign up to set email alerts
|

Human Pupillary Dilation Response to Deviant Auditory Stimuli: Effects of Stimulus Properties and Voluntary Attention

Abstract: A unique sound that deviates from a repetitive background sound induces signature neural responses, such as mismatch negativity and novelty P3 response in electro-encephalography studies. Here we show that a deviant auditory stimulus induces a human pupillary dilation response (PDR) that is sensitive to the stimulus properties and irrespective whether attention is directed to the sounds or not. In an auditory oddball sequence, we used white noise and 2000-Hz tones as oddballs against repeated 1000-Hz tones. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 50 publications
10
87
1
Order By: Relevance
“…45 In the present study, pupil size provides the closest analogy to eye tracking while mouse movements are analogous to mouse tracking. Consistent with previous results in audio and vision studies, [47][48][49] our analysis shows that when a salient stimulus is received, pupils naturally dilate to try to absorb as much information as possible. However, using the complex scenes employed in the current study sheds light on a more nuanced relationship between pupil dilations and auditory salience.…”
Section: Discussionsupporting
confidence: 78%
“…45 In the present study, pupil size provides the closest analogy to eye tracking while mouse movements are analogous to mouse tracking. Consistent with previous results in audio and vision studies, [47][48][49] our analysis shows that when a salient stimulus is received, pupils naturally dilate to try to absorb as much information as possible. However, using the complex scenes employed in the current study sheds light on a more nuanced relationship between pupil dilations and auditory salience.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to neuroimaging techniques, we acquired pupillometry data, as it reflects LC activity (Joshi, Li, Kalwani, & Gold, 2015;Reimer et al, 2016) and provides a sensitive metric of phasic responses to oddballs (Liao, Yoneya, Kidani, Kashino, & Furukawa, 2016;Murphy et al, 2014). Recordings of LC neurons in monkeys have found that LC neurons activate in response to infrequent target stimuli in visual oddball tasks, but respond only weakly or not at all to more frequent non-target items (for review see Nieuwenhuis, Aston-Jones, & Cohen, 2005).…”
Section: Pupillometry As An Indirect Marker Of Lc Activitymentioning
confidence: 99%
“…Beside the well-known response of pupillary muscles to light, allowing to narrow the range of light intensity reaching the retina and optimizing its information capacity [1], pupil size varies also as a function of a wealth of cognitive phenomena, including mental effort [2,3,4,5], surprise [6,7,8,9,10,11,12,13,14,15], emotion [16], decision processes [17,18,19,20], decision biases [21,19,22], value beliefs [23,24,25], volatility (unexpected uncertainty; [26,27,28,10], exploitation/exploration trade-off [29,30], attention [31,32,33,34,35,36], uncertainty [37,19,38,12,21,23,25], confidence [39], response to reward [40], learning rate [41,…”
Section: Cognitive Pupillary Responsementioning
confidence: 99%
“…when GO was defined by the occurrence of 1-letter as opposed to 2-letter stimuli, the identity of the letter being presented was irrelevant and failed to affect pupil response; see simulated results in figure 1). More generally, several studies have found that pupillary responses to stimuli depend on whether they are attended to or not [31,32,34,55,56] and that these responses scale with the subjective salience of the stimuli [35,56,57]. In attentional blink experiments, targets that follow closely previous target occurrences remain sometimes undetected.…”
Section: Information About Task Variablesmentioning
confidence: 99%